IMPLEMENTASI PROGRAM KELUARGA HARAPAN BIDANG PENDIDIKAN (STUDI KASUS DI DESA SUNGAI MALAYA KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA) - MU'AMMAR KADAFI (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2021)
The purpose of this study is to describe and analyze the Implementation Process of the Family Hope Program in Education in Sungai Malaya Village, Sungai Ambawang District, Kubu Raya Regency. This type of research is descriptive using a qualitative approach. In this study, researchers used the concept of the theory of Erwan Agus Purwanto and Dyah Ratih Sulistyastuti related to the implementation of policies that cover 3 (three) basics namely; Dissemination, Delivery Activities and Utilization of Policy Output as a knife for analysis. The Hope Family Implementation Program (PKH) in Education in Sungai Malaya Village, Ambawang River District, Kubu Raya Regency has not been running optimally in accordance with PKH objectives, there are still recipients who do not match the benefits of PKH. The cause of the socialization aspect is the perceived constraints based on the region of residence. Deficiencies in infrastructure create obstacles in their implementation. Aspects of Delivery Activities Program Family Expectations for some people are right on target. But there are still people who are entitled to this program don't get it. Regarding PKH beneficiaries, the Regency government did not take part in it, all based on data submitted and determined by the central party. Aspects of Utilizing Policy Output are still being found students clothes that are not appropriate to wear and attendance attendance that is not optimal. The Family Hope Program Companion suggestion is expected to work well so that the Family Hope Program that has been determined can run well, such as socialization, initial data collection, validation and reporting every month.